2002
DOI: 10.1039/b108682k
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposures and microenvironmental concentrations of particles and bioaerosols

Abstract: The aim of this study was to compare the personal exposure to particles and bioaerosols with that measured by stationary samplers in the main microenvironments, i.e., the home and the workplace. A random sample of 81 elementary school teachers was selected from the 823 teachers working for two councils in eastern Finland for the winter time measurement period. Bioaerosol and other particles were collected on filters by button samplers using personal sampling and microenvironmental measurements in homes and wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 49 publications
2
100
0
2
Order By: Relevance
“…It should be noted that measurements reported in the above-cited papers were conducted in environments with extremely high levels of the fungal spore concentration: up to 10 10 spores m -3 and 10 10 CFU m -3 . Toivola et al (2002) measured the fungal spore culturability in a personal exposure study performed in winter in Finland. The investigators found very low culturability levels (below 1% on the average) that may be attributed to low longterm air temperatures outdoors during their measurements.…”
Section: Culturabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that measurements reported in the above-cited papers were conducted in environments with extremely high levels of the fungal spore concentration: up to 10 10 spores m -3 and 10 10 CFU m -3 . Toivola et al (2002) measured the fungal spore culturability in a personal exposure study performed in winter in Finland. The investigators found very low culturability levels (below 1% on the average) that may be attributed to low longterm air temperatures outdoors during their measurements.…”
Section: Culturabilitymentioning
confidence: 99%
“…Thus, we believe that the airborne fungi should be collected for the CFU and total enumeration using the same sampler and the same collection media. E.g., Toivola et al (2002) utilized filter collection of airborne microorganisms with subsequent extraction for culturable and total fungi.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant indoor (cultivable) airborne bacteria are gram-positive cocci, such as Micrococcus and Staphylococcus, which represented 38% of the composition of airborne bacteria discovered in a survey of 100 buildings in the USA while they equaled 100% of what was found inside the sampled dwellings in a Poland study (Górny and Dutkiewicz 2002;Tsai and Macher 2005). It is noted that culture-based techniques can identify less than 1% of the indoor microbial community and instead indentify the species that are easily cultured (Toivola et al 2002). Micrococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Study protocol, measurement, and sample analysis techniques are presented in detail by Toivola et al (2002Toivola et al ( , 2004a, and are only shortly described below. A random sample of 81 elementary school teachers was selected from the total of 823 teachers working in eastern Finland.…”
Section: Methodsmentioning
confidence: 99%
“…Along with the exposure measurements, health questionnaire data was collected from the studied individuals. Therefore, this study focused on analyzing the health data, whereas the detailed analyses of the exposure data is reported elsewhere (Toivola et al, 2002(Toivola et al, , 2004a. The specific aims of this study were to (1) study the agreement between questionnaire responses when using different recall periods, and (2) study the associations between elementary school teachers' health symptoms and both personal and microenvironmental concentrations of particles and microbial aerosol.…”
Section: Introductionmentioning
confidence: 99%